The Axiological Aspects of Science in the Thought of Ibn Khaldun - Putawa, Rilliandi Arindra (Jurnal Usuluddin, 2024)
The study of the philosophy of science in the world of Islamic philosophy is still relatively rare. However, there are many great Islamic philosophers in the past who have contributed to the understanding of scientific development during their time. Ibn Khaldun, as one of the greatest Islamic thinkers, has made significant contributions to the development of various fields of knowledge. One area of study that has attracted Ibn Khaldun’s attention is related to scientific development. Ibn Khaldun’s own focus is on various scientific problems that occurred during his lifetime, including those related to value issues. Axiology of science as a branch of the philosophy of science focusing on value issues within science is a new approach that is still rarely found in studies related to Islamic thought. This research will attempt to explore Ibn Khaldun’s thoughts related to the field of Axiology of Science through a literature review of Ibn Khaldun’s major work, the Muqaddimah. The results of the study indicate that many of Ibn Khaldun’s philosophical thoughts touch on the relationship between values and science, such as the values of divinity, economics, and politics. Economic values can influence the direction of scientific development, while political values can be influenced by the activities of scientists. The misuse of scientific knowledge for evil purposes has also developed and been highlighted by Ibn Khaldun during that period. This indicates an awareness of moral aspects among scientists at that time.